Effect of spiral split ring resonator (S-SRR) structure on truncated pyramidal microwave absorber design - Nornikman, H. (2012)
This paper discusses on the effect of the spiral split ring resonator on the truncated pyramidal microwave absorber. Split ring resonator (SRR) structure can potentially be incorporated onto the truncated pyramidal microwave absorber to increase the reflection loss performance. There are many ways to increase the pyramidal microwave absorber performance. The ways are focusing the new hybrid shapes, using high carbon material, and adding the left handed material structure on the pyramid microwave absorber. Left handed material or metamaterial is an artificial material that does not exist in the real nature like FR4, Taconic, Rogers or RT Duriod.